Hurricane Katrina - Finch, Fletcher C. (History just before you were born., 2019)
Describes the deadly effects of Hurricane Katrina on the city of New Orleans in 2005. Discusses the storm's power, rescue efforts, the chaos and violence that ensued, and the rebuilding process. Includes color photographs, fact boxes, sidebars, a timeline, a glossary, and further resources.